Association of Socioeconomic Status and Overweight/Obesity in Rural-to-Urban Migrants: Different Effects by Age at Arrival - Wang, Ye; Pan, Li; Wan, Shaoping; Yi, Huowuli; Yang, Fang; He, Huijing; Li, Zheng; Yong, Zhengping; Shan, Guangliang (Frontiers in Public Health, 2020)
This study aims to investigate the association between socioeconomic status and overweight/obesity in rural-to-urban Yi migrants in China, and to explore whether the association varied by the age at arriving urban areas. The cross-sectional population-based data from the Yi Migrants Study in 2015 was used, which included 1,181 Yi migrants aged 20–80 years. Socioeconomic status was evaluated by education level, personal annual income, and a composited variable (socioeconomic status index, SESI). Measured weight and height were used to calculate BMI and to define overweight/obesity (BMI ≥ 24 kg/m2). The results suggested that the association of income and SESI with overweight/obesity was not significant when age at arrival (two groups, <20 and ≥20 years) was considered as a covariate. In the stratification analysis, reversed association was observed in the two groups of age at arrival. In migrants of <20 years of age at arrival, higher level of education and SESI were related to decreased risk of overweight/obesity. In contrary, in those of ≥20 years at arrival, higher socioeconomic status level was found to be related to increased risk. Our findings suggest that the effect of socioeconomic status on overweight/obesity was modified by the age at arrival in Yi migrants. Especially, the association between socioeconomic status and overweight/obesity was negative when migration before 20 years of age, and transfer to positive after 20 years.